Reading Newton in early modern Europe - Boran, Elizabethanne; Feingold, Mordechai (History of science and medicine library. Scientific and learned cultures and their institutions, 2017)
Reading Newton in Early Modern Europe investigates how Sir Isaac Newton's Principial was read, interpreted and remodelled for a variety of readerships in eighteenth-century Europe. The editors, Mordechai Feingold and Elizabethanne Boran, have brought together papers which explore how, when, where and why the Principial was appropriated by readers in Italy, Spain, the Netherlands, England and Ireland. Particular focus is laid on the methods of transmission of Newtonian ideas via university textbooks and popular works written for educated laymen and women. At the same time, challenges to the Newtonian consensus are explored by writers such as Marius Stan and Catherine Abou-Nemeh who examine Cartesian and Leibnizian responses to the Principial. Eighteenth-century attempts to remodel Newton as a heretic are explored by Feingold, while William R. Newman draws attention to vital new sources highlighting the importance of alchemy to Newton.